The interconnection of hierarchy, affiliative behaviours, and social play shapes social dynamics in Maremmana beef cattle - Bagnato, Samuel; Pedruzzi, Luca; Goracci, Jacopo; Palagi, Elisabetta (Applied animal behaviour science, 2023)
Dominance hierarchies can be interconnected with behaviours that are essential to manage social living, such as affiliative behaviours and social play, whose importance can already emerge in the early phases of life. Here, we carried out an observational study (all occurrences sampling) to investigate the possible interconnection between these three behavioural categories in a group of Maremmana beef cattle (n = 44, 6–21 months of age) in an extensive breeding system. We found that a clearly linear hierarchy is present in the group, and that the age of the animals positively correlated with their hierarchical ranks. Affiliative behaviours were directed up to the hierarchy: dominants received more affiliative behaviours and subordinates were generally starting the sessions, suggesting that affiliative behaviours may be used by subordinates to bond with dominants for possibly gaining some benefits. Social play mainly consisted of play fighting and dominant subjects played with the highest frequency. However, playful modality was independent from playmates’ relative rank position, with longer-lasting sessions being characterized by unbalanced and unreciprocated patterns. This indicates that play fighting in cattle has a competitive rather than cooperative nature and that it may be used as physical training to develop competitive skills in all groupmates. When play fighting was punctuated by affiliative behaviours, the playful sessions lasted longer. In this view, affiliative behaviours can have a communicative value useful in downgrading the competition emerging during play fighting. In conclusion, under naturalistic conditions young animals of beef cattle express all the behavioural repertoire typical of adulthood and their agonistic, affiliative, and playful behaviours are strongly interconnected in shaping social dynamics. Thus, our study suggests that extensive farming conditions are ideal to study the behavioural strategies domestic animals enact to form cohesive social groups. Such information is needed to enhance management and welfare of domestic ungulates. •Extensively raised beef cattle form groups with a linear dominance hierarchy.•The oldest animals occupy the top positions of the hierarchy.•Affiliative behaviours follow rank rules and fine-tune play sessions.•Play fighting has a competitive and training nature but does not follow rank rules.